Adherence to the Mediterranean diet and mortality in cancer survivors: a Nationwide study with mediation and subgroup analyses - Zha, Bowen; Dou, Lizhou; Zhang, Chen; He, Shun; Wang, Guiqi (Frontiers in Nutrition, 2025)
BackgroundMediterranean diet (MD) adherence is linked to improved health outcomes, yet evidence among cancer survivors remains limited. This study investigated the association between Mediterranean Diet Score (MDS) adherence and all-cause mortality among cancer survivors.MethodsWe analyzed data from 2,669 cancer survivors participating in the National Health and Nutrition Examination Survey (2005–2018). Dietary adherence was assessed using the MDS based on 2-day dietary recalls. Multivariable Cox regression, mediation, subgroup, and sensitivity analyses were conducted.ResultsHigher MDS adherence was significantly associated with reduced all-cause mortality (hazard ratio (HR) = 0.845, 95% confidence interval (CI): 0.779–0.917, p < 0.001), with a linear dose–response trend. Mediation analysis showed that red blood cell distribution width and neutrophils explained 18.5 and 7.8% of the association, respectively. Subgroup analyses revealed stronger protective effects in females, older adults, individuals with lower BMI or higher socioeconomic status, smokers, drinkers, and survivors of digestive, urinary, and skin cancers. Sensitivity analyses confirmed the robustness of the findings.ConclusionGreater adherence to the Mediterranean diet is associated with lower all-cause mortality in cancer survivors, partly mediated by inflammatory biomarkers. Integrating Mediterranean dietary counseling into survivorship care may help improve long-term outcomes.